2012
DOI: 10.2478/s11658-012-0031-6
|View full text |Cite
|
Sign up to set email alerts
|

The human telomerase catalytic subunit and viral telomerase RNA reconstitute a functional telomerase complex in a cell-free system, but not in human cells

Abstract: Abstract:The minimal vertebrate telomerase enzyme is composed of a protein component (telomerase reverse transcriptase, TERT) and an RNA component (telomerase RNA, TR). Expression of these two subunits is sufficient to reconstitute telomerase activity in vitro, while the formation of a holoenzyme comprising telomerase-associated proteins is necessary for proper telomere length maintenance. Previous reports demonstrated the high processivity of the human telomerase complex and the interspecies compatibility of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Further, TRs in land plants have a monophyletic origin [19]. This contradicts the previous paradigm, according to which relatively conserved TERT subunits associate with very diverse-and unrelated-RNAs [57,58].…”
Section: Rna Subunit Of Telomerasementioning
confidence: 84%
See 1 more Smart Citation
“…Further, TRs in land plants have a monophyletic origin [19]. This contradicts the previous paradigm, according to which relatively conserved TERT subunits associate with very diverse-and unrelated-RNAs [57,58].…”
Section: Rna Subunit Of Telomerasementioning
confidence: 84%
“…It was proposed that telomerase originated as an ancient reverse transcriptase (RT) that internalized a primitive template-bearing RNA during early eukaryotic evolution, and later evolved into modern telomerase ribonucleoproteins (RNPs) with various indispensable and stably TR-associated components [ 55 , 56 ]. In accordance with this notion, the TERT subunit has the ability to bind not exclusively the RNA molecule that provides the template sequence for DNA synthesis (TR), but also various non-telomeric sequences [ 57 , 58 ]. The conserved RT motifs between TERT and other RTs indicates that the TERT protein is closely related to RTs from the group of Penelope-like Elements (PLEs) and non-long-terminal-repeat (non-LTR) retrotransposons [ 55 ].…”
Section: The Origin Of Telomerasementioning
confidence: 99%
“…Thus, a single-strand overhang is produced. The common DNA polymerase then synthesizes the complementary strand after the dissociation of the telomerase holoenzyme [10][11][12][13][14]. This produces the telomere, a specialized DNA structure that gathers a plethora of proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies suggest that the minimal requirement for the normal activity of telomerase in vitro is the expression of both hTR and hTERT. However, the common belief is that the regulation and proper activity of telomerase in vivo is complex, multistep procedure that involves many other proteins as well [10][11][12][13]. When the telomere length reaches a critical point, the RNA component (hTR) provides the template and then the reverse transcriptase (hTERT) synthesizes DNA with its own RNA unit as the source.…”
Section: Introductionmentioning
confidence: 99%
“…The secondary structures of vTR, cTR, and hTR are highly conserved, including the pseudoknot (core) domain that harbors the template sequence (CR-1) for the extension of telomeric repeats ( 15 ), the CR4-CR5 domain that is essential for proper assembly with TERT ( 15 ) and the H/ACA box and CR-7 domain, which are responsible for TR stability and localization ( 13 , 16 , 17 ). In addition, we showed that both vTR and hTR interact with chicken TERT and mediate telomerase activity in vitro ( 18 ). Therefore, we investigated whether overexpression of hTR could complement the loss of vTR in MDV-induced tumorigenesis and whether vTR possesses anti-apoptotic functions.…”
Section: Introductionmentioning
confidence: 99%